Changes in teachers' epistemic cognition about self–regulated learning as they engaged in a researcher-facilitated professional learning community. Issue 2 (14th March 2020) - Barr, Shyam; Askell-Williams, Helen
ABSTRACT: Research into teachers' epistemic cognition is emerging as a key to understanding the quality of teachers' knowledge for teaching. Typically, investigations into the quality of teachers' knowledge have been situated within traditional subject areas, such as science or maths. However, developing good quality teacher knowledge about improving students' abilities to engage in self-regulated learning (SRL), across subject areas, is equally important. Studies have demonstrated gaps in teachers' knowledge and epistemic beliefs about SRL – the foundations for teachers' epistemic cognition about SRL. This paper introduces a model of teachers' epistemic cognition about SRL, and reports a micro-analytic study with four secondary science teachers who undertook a 12-week researcher-facilitated Professional Learning Community (PLC). Thematic and numerical analysis of interviews and lesson plans indicated that the PLC facilitated teachers' reflexive examination of their knowledge and their epistemic beliefs about SRL. Improvements in SRL content knowledge, pedagogical content knowledge and constructivist beliefs were observed consistently for three of the four teachers. Providing opportunities, such as a facilitated PLC, to enable teachers to reflexively examine their epistemic cognition about a generic subject such as SRL, may be a necessary step in translating research about learning and instruction into classroom practices.